The deaf divide - Kham, Priscilla (2014)
An era is ending for Singapore’s deaf education. Students who need to sign no longer have a special environment to learn. The Singapore School for the Deaf, home to five decades of Deaf culture and history, is set to close in 2016. This comes after more than a decade of falling enrolment as more deaf children enter mainstream schools, with hearing aids and cochlear implants enabling them to speak. But amidst this phenomenon are dissenting voices. At the heart of the issue lies a debate between sign language and speaking. With speech, a deaf person is no longer seen as disabled in a society that prizes fitting in. But in this pursuit to integrate with the hearing world, sign language — touted by deaf advocates as crucial for cognitive development and identity building — is being set aside as the last resort.